Letter - Short, J. B.
032-0158-001 POTATO MARKETING BOARD AFRICA HOUSE KINGSWAY LONDON, W.C.2 TELEPHONE HOLBORN 9512 TELEGRAMS "POTABOR WESTCENT, LONDON" SECRETARY: E.C. BOUGHTON REF.: 0215/1 3rd January, 1938. Please address reply to the marketing officer. H.V. Tewson, Esq., Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1. Dear Sir, In confirmation of the information which I gave to Mr. Woodcock when he called to see me this afternoon, I can say that the Potato Marketing Board would be prepared to sell a substantial quantity of potatoes to you at between 25/- to 30/- per ton free on board in free bags, provided that this order materialises within the next few days and that delivery can be completed within 14 to 21 days from today's date. Yours faithfully, J. B. Short, Marketing Officer. JBS/HS C.W.S. 45/9 ton c.i.f. Rouen 292/946/32/158